Från nationalhjälte till rikstyrann: Karl XII i det svenska 1800-talets litterära minneskultur - Bak, Krzysztof (Scandinavistica Vilnensis, 2023)
The overall aim of the article is to investigate the structure and dynamics of the Swedish cultural memory in the nineteenth century. According to the micrological methodology, recommended by leading theorists of cultural memory, the article focuses on five representative texts: three Romantic poems written to the 1818 centenary of Charles XII’s death (Bernhard von Beskow’s “Carl den Tolfte,” Erik Gustaf Geijer’s “Ord till Karl XII:s marsch vid Narva,” and Esaias Tegnér’s “Carl XII”), and two short stories, written in the last decade of the nineteenth century, both depicting the events immediately after the death of Charles XII and thus thematising the cultural memory of the king as communicative memory (Verner von Heidenstam’s “En hjältes likfärd” and August Strindberg’s “Vid Likvakan i Tistedalen”). Analysing the three poems, the article makes an attempt to reconstruct the degree zero structure of the Swedish cultural memory in the nineteenth century. It is argued that the poems’ cultural memory has an eclectic character and requires a kind of archaeological approach. In the first step, the article identifies a tissue of elements, belonging to the pre-industrial cultural memory: cult of the death, burial scenery, relic, fame, ritualization, militarization. The poems subordinate this archaic memory system to the structures which are the products of the nineteenth century and originate from one single social process: industrialization. In the second step, the main part of the article, these industrial components of the poems’ cultural memory are analysed: subjectification, temporalization, historicization, productivization, nationalization, and finally mythicization – the final component is investigated using both Barthesian and Jungian conceptual apparatus. In the third and last step, the article studies the development of this degree zero memory structure during the nineteenth century. Two main evolutionary trends, rooted in two different modifications of the Kantian notion of the Self, are distinguished. The first trend, exemplified by the short story of Heidenstam, implies an existential psychologization of the industrial cultural memory. The second trend, represented by the short story of Strindberg, is based on a naturalistic correction of the Kantian Self and executes a subversive demythicization of the Romantic Charles XII-myth.